2008
DOI: 10.1111/j.1365-294x.2007.03624.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of coastal topography, circulation patterns, and rafting in structuring populations of an intertidal alga

Abstract: Understanding the dispersal processes that influence genetic structure in marine species requires estimating gene flow in a dynamic, fluid environment that is often poorly characterized at scales relevant to multiple dispersive stages (e.g. spores, gametes, zygotes, larvae, adults). We examine genetic structure in the marine alga Fucus vesiculosus L., which inhabits moderately exposed shores in the northern Atlantic but releases gametes only under sunny, calm conditions. We predicted genetic structure would co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 82 publications
1
50
0
Order By: Relevance
“…For example, European and North American populations of the isopod Idotea baltica are closely related to each other, suggesting rafting dispersal across the North Atlantic (Wares, 2001). Similarly, Muhlin et al (2008) found that in the Gulf of Maine (NW Atlantic) reproductive fragments of Fucus vesiculosus floating in coastal currents can explain the genetic pattern of this intertidal seaweed. For the North Sea coasts, Reusch (2002) suggested that rafting shoots of Zostera marina can explain the low genetic variability among populations of this seagrass (distance b150 km, see also Olsen et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, European and North American populations of the isopod Idotea baltica are closely related to each other, suggesting rafting dispersal across the North Atlantic (Wares, 2001). Similarly, Muhlin et al (2008) found that in the Gulf of Maine (NW Atlantic) reproductive fragments of Fucus vesiculosus floating in coastal currents can explain the genetic pattern of this intertidal seaweed. For the North Sea coasts, Reusch (2002) suggested that rafting shoots of Zostera marina can explain the low genetic variability among populations of this seagrass (distance b150 km, see also Olsen et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…seaweed and wood) and anthropogenic debris (e.g. plastics items) have been suggested as dispersal vectors for a wide range of species from marine and terrestrial environments (Ingólfsson, 1995;Barnes and Milner, 2005;Johansen and Hytteborn, 2001;Waters, 2008); recent molecular studies have added support to this view (Muhlin et al, 2008;Nikula et al, 2010). Anthropogenic floating objects (mainly plastic debris) may facilitate long-distance dispersal of invasive species, and furthermore impact marine wildlife (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…First, dispersal may be increased via transport of floating, fertile material that is removed from the substratum during storms. Propagules from fertile algal wrack may be viable for long periods following detachment (Macaya et al 2005, Hernández-Carmona et al 2006, Muhlin et al 2008, and dispersal of floating wrack of other species of fucoid algae has been sug- It is interesting that no pattern of isolation by distance or spatial autocorrelation exists for Phyllospora at scales > 80 km. The apparent patchiness of genetic structure of Phyllospora may be due to fine-scale oceanographic features such as eddies that break off the East Australian Current (EAC).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous growth and production of viable zoospores from M. pyrifera rafts along the Chilean coast has been reported (Macaya et al 2005). Similarly, rafting of storm-detached thalli of Fucus vesiculosus, which release gametes when deposited at a new site, has been proposed to lead to connectivity between populations (Muhlin et al 2008), and dispersal by floating thalli has been suggested for other macroalgal species (e.g., Dayton 1973, van den Hoek 1987, McKenzie & Bellgrove 2008, Fraser et al 2009, and see review by Thiel & Gutow 2005).…”
Section: Genetic Diversity and Dispersal Potentialmentioning
confidence: 99%